Paleoenvironmental changes in the northern shelf of the Sea of Okhotsk during the Holocene. - Gorbarenko, Sergey A; Tsoy, Ira B; Astakhov, Anatoly S; Artemova, Antonina V; Gvozdeva, I G; Annin, V K; Rasskazov, S V (PANGAEA, 2007)
The combined micropaleontological (spores and pollen, diatoms, benthic foraminifers), lithologic, and isotopic-geochemical analysis of sediments from the northern shelf of the Sea of Okhotsk recovered by hydrostatic corer from the depth of 140 mbsl elucidated environmental changes in this part of the basin and adjacent land areas during the last 12.7 thousands cal. years. Geochronological scale of the core is established using the acceleration mass-spectrometry method for radiocarbon dating of benthic Foraminifera tests. The first insignificant warming in the northern part of the sea after glaciation occurred in the mid-Boreal time (9.6 ka ago) but not at the onset of the Holocene. The strongest warming in the region took place in the mid-Atlantic epoch to reach climatic optimum in the second half of the Subboreal (6 to 2.5 ka ago). A cooling in the northern shelf and adjacent land areas is established at the beginning of the Subatlantic (2.5 ka). A comparison of results obtained for Core 89211 with dated hydrological and climatic changes in central and southern parts of the Sea of Okhotsk (Gorbarenko et al., 2003, 2004) is used for a high-resolution analysis of climatic fluctuations in the study region and other areas of the basin during deglaciation and the Holocene.
Ages of sediments from Core MG34-89211, northern shelf of the Sea of Okhotsk
Keywords: Age, 14C milieu/reservoir corrected; Age, dated; Age, dated standard deviation; Analytical method; Archive of Ocean Data; ARCOD; BC; Box corer; Calendar age; DEPTH, sediment/rock; MG34; MG34-89211; Morskoy Geophysik; Sample, optional label/labor no; Sample type; Sea of Okhotsk